CXCR5+ CD8 T Cells: Protective or Pathogenic? - Valentine, Kristen M.; Hoyer, Katrina K. (Frontiers in Immunology, 2019)
CD8 T cells are infrequently considered part of germinal center reactions. Yet, a distinct CXCR5+ CD8 T cell subset identified within the B cell follicle and germinal center in situations of chronic antigen has recently been defined. CXCR5+ CD8 T cells maintain transcriptional and phenotypic features consistent with the CD8 T cell nomenclature of a non-exhausted, effector memory population. CD8 T cell localization to the B cell follicle suggests a functional profile similar to CD4 T follicular helper cells that are licensed to promote B cell responses. The functional mechanisms defined under different immune settings, while largely similar, differentially control disease pathogenesis. CXCR5+ CD8 T cells control viral load during infection, and also promote antibody-mediated autoimmune disease progression. The existence of this novel CXCR5+ CD8 T cell subset in human and murine models of disease may provide a paradigm shift in our understanding of germinal center reactions